2001
DOI: 10.1152/ajpregu.2001.281.2.r459
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and renal effects of intravascular volume expansion in compensated heart failure

Abstract: To examine if the neuroendocrine link between volume sensing and renal function is preserved in compensated chronic heart failure [HF, ejection fraction 0.29 +/- 0.03 (mean +/- SE)] we tested the hypothesis that intravascular and central blood volume expansion by 3 h of water immersion (WI) elicits a natriuresis. In HF, WI suppressed ANG II and aldosterone (Aldo) concentrations, increased the release of atrial natriuretic peptide (ANP), and elicited a natriuresis (P < 0.05 for all) compared with seated control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…Despite a higher CI, MAP remained unchanged because of compensatory peripheral vasodilatation (Table 3). Our results are in accordance with recent studies of medically treated patients with compensated HF in which acute central intravascular volume expansion elicited a hemodynamic, neuroendocrine, and renal response similar to that of normal controls (7,8).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Despite a higher CI, MAP remained unchanged because of compensatory peripheral vasodilatation (Table 3). Our results are in accordance with recent studies of medically treated patients with compensated HF in which acute central intravascular volume expansion elicited a hemodynamic, neuroendocrine, and renal response similar to that of normal controls (7,8).…”
Section: Discussionsupporting
confidence: 92%
“…These findings oppose the results of previous studies, in which untreated and conventionally (digoxin) treated patients with HF have been shown to accumulate sodium and water in excess during dietary sodium loading (2, 4, 14, 27, 30). However, it was recently demonstrated that monotherapy with ACE inhibitors restores renal sodium excretion during acute volume expansion in compensated HF (7). Hence, it is conceivable that the neuroendocrine link, which senses the intravascular volume expansion induced by high sodium intake and promotes renal sodium excretion, is preserved in medically treated HF patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the upright seated control position, water immersion increased stroke volume index and decreased vascular resistance. 20,21 Thus, the circulatory condition in the heart failure patients improved. Because our results presented here from parabolic flights and spaceflight are in compliance with those of water immersion, 20,21 it is fair to conclude that gravity is a constant burden for heart failure patients and that it aggravates their condition.…”
Section: Perspectivesmentioning
confidence: 99%
“…E-mail khildenbrand@wsu.edu. heart injury (Gabrielsen et al, 2001;Gabrielsen, Sorensen et al, 2000;Hanna, Sheldahl, & Tristani, 1993;Heigenhauser, Boulet, Miller, & Faulkner, 1977;Jiang et al, 1994;Magder, Linnarsson, & Gullstrand, 1981;McMurray, Avery, & Sheps, 1988;Meyer & Leblanc, 2008).…”
Section: Water Immersion and The Bodymentioning
confidence: 99%